Lung-Adapted Staphylococcus aureus Isolates With Dysfunctional Agr System Trigger a Proinflammatory Response . (7th May 2022) - Ramond, Elodie; Lepissier, Agathe; Ding, Xiongqi; Bouvier, Clémence; Tan, Xin; Euphrasie, Daniel; Monbernard, Pierre; Dupuis, Marion; Saubaméa, Bruno; Nemazanyy, Ivan; Nassif, Xavier; Ferroni, Agnès; et al.
Abstract: Background: Staphylococcus aureus dominates the lung microbiota of children with cystic fibrosis (CF) and persistent clones are able to establish chronic infection for years, having a direct deleterious impact on lung function. However, in this context, the exact contribution of S. aureus to the decline in respiratory function in children with CF is not elucidated. Methods: To investigate the contribution of persistent S. aureus clones in CF disease, we undertook the analysis of sequential isogenic isolates recovered from 15 young CF patients. Results: Using an air-liquid infection model, we observed a strong correlation between S. aureus adaption in the lung (late isolates), low toxicity, and proinflammatory cytokine secretion. Conversely, early isolates appeared to be highly cytotoxic but did not promote cytokine secretion. We found that cytokine secretion was dependent on staphylococcal protein A (Spa), which was selectively expressed in late compared to early isolates as a consequence of dysfunctional agr quorum-sensing system. Finally, we demonstrated the involvement of TNF-α receptor 1 signaling in the inflammatory response of airway epithelial cells to these lung-adapted S. aureus isolates. Conclusions: Our results suggest an unexpected direct role of bacterial lung adaptation in the progression of chronic lung disease by promoting a proinflammatory response through acquired agr dysfunction. Abstract : In cystic fibrosis patients, S. aureus lung-adapted variants evolve towards toxin silencing with an unexpected increased capacity to promote inflammation. This remarkable observation reveals an unanticipated direct role of S. aureus in the progression of the disease.